A gene therapeutic approach to inhibit calcium and integrin binding protein 1 ameliorates maladaptive remodelling in pressure overload. Issue 1 (20th June 2018) - Grund, Andrea; Szaroszyk, Malgorzata; Döppner, Janina K; Malek Mohammadi, Mona; Kattih, Badder; Korf-Klingebiel, Mortimer; Gigina, Anna; Scherr, Michaela; Kensah, George; Jara-Avaca, Monica; Gruh, Ina; Martin, Ulrich; et al.
Abstract: Aims: Chronic heart failure is becoming increasingly prevalent and is still associated with a high mortality rate. Myocardial hypertrophy and fibrosis drive cardiac remodelling and heart failure, but they are not sufficiently inhibited by current treatment strategies. Furthermore, despite increasing knowledge on cardiomyocyte intracellular signalling proteins inducing pathological hypertrophy, therapeutic approaches to target these molecules are currently unavailable. In this study, we aimed to establish and test a therapeutic tool to counteract the 22 kDa calcium and integrin binding protein (CIB) 1, which we have previously identified as nodal regulator of pathological cardiac hypertrophy and as activator of the maladaptive calcineurin/NFAT axis. Methods and results: Among three different sequences, we selected a shRNA construct (shCIB1) to specifically down-regulate CIB1 by 50% upon adenoviral overexpression in neonatal rat cardiomyocytes (NRCM), and upon overexpression by an adeno-associated-virus (AAV) 9 vector in mouse hearts. Overexpression of shCIB1 in NRCM markedly reduced cellular growth, improved contractility of bioartificial cardiac tissue and reduced calcineurin/NFAT activation in response to hypertrophic stimulation. In mice, administration of AAV-shCIB1 strongly ameliorated eccentric cardiac hypertrophy and cardiac dysfunction during 2 weeks of pressure overload by transverse aortic constriction (TAC). Ultrastructural and molecular analyses revealed markedly reduced myocardial fibrosis, inhibition of hypertrophy associated gene expression and calcineurin/NFAT as well as ERK MAP kinase activation after TAC in AAV-shCIB1 vs. AAV-shControl treated mice. During long-term exposure to pressure overload for 10 weeks, AAV-shCIB1 treatment maintained its anti-hypertrophic and anti-fibrotic effects, but cardiac function was no longer improved vs. AAV-shControl treatment, most likely resulting from a reduction in myocardial angiogenesis upon downregulation of CIB1. Conclusions: Inhibition of CIB1 by a shRNA-mediated gene therapy potently inhibits pathological cardiac hypertrophy and fibrosis during pressure overload. While cardiac function is initially improved by shCIB1, this cannot be kept up during persisting overload.